MY SAY: Goodbye, ‘Eyeraq’ - Abd Razak, Dzulkifli (2010)
As the Iraqis busied themselves with election day to determine the future of their country, many were asking what they would be voting for. Freedom? Security? Fortune? Or just another socalled democratic exercise? They have done this many times since the invasion, but as in other far more stable countries, elections stopped short of delivering "democracy".